Textile dyes wastewater - Nor Hazhar, Nurul Jihan; Abduh Algheethi, Adel Ali Saeed; Abdul Kadir, Aeslina; Sarani, Noor Amira (Penerbit UTHM, 2021)
Dyes are coloured complex organic compounds with complicated structures and the highly coloured wastewater produced, contaminated with dyeing and other chemical auxiliaries. However, the technologies introduced ways that could be practiced in removing these contaminated materials to save the environment were discussed. Nevertheless, alternative green methods that could be used to remove the dyes from industrial wastewater were also highlighted to save the environment.